2002
DOI: 10.1074/jbc.m200925200
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Stratum Corneum Hydration in Mice Lacking Epidermal Water Channel Aquaporin-3

Abstract: The water and solute transporting properties of the epidermis have been proposed to be important determinants of skin moisture content and barrier properties. The water/small solute-transporting protein aquaporin-3 (AQP3) was found by immunofluorescence and immunogold electron microscopy to be expressed at the plasma membrane of epidermal keratinocytes in mouse skin. We studied the role of AQP3 in stratum corneum (SC) hydration by comparative measurements in wildtype and AQP3 null mice generated in a hairless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
201
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(213 citation statements)
references
References 38 publications
7
201
0
5
Order By: Relevance
“…AQP3 is expressed in the basal layer of keratinocytes and is thought to transport glycerol to the epidermis in response to dermal-to-epidermal gradient. Previous studies on Aqp3 null mice showed reduced glycerol content in the epidermis and impaired skin elasticity, barrier recovery, and wound healing, but normal serum glycerol concentrations (34)(35)(36). On the other hand, AQP9 is expressed in the liver and coordinately regulated with AQP7 in response to fasting͞feeding (15).…”
Section: Discussionmentioning
confidence: 99%
“…AQP3 is expressed in the basal layer of keratinocytes and is thought to transport glycerol to the epidermis in response to dermal-to-epidermal gradient. Previous studies on Aqp3 null mice showed reduced glycerol content in the epidermis and impaired skin elasticity, barrier recovery, and wound healing, but normal serum glycerol concentrations (34)(35)(36). On the other hand, AQP9 is expressed in the liver and coordinately regulated with AQP7 in response to fasting͞feeding (15).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian skin, AQP3 is expressed strongly in plasma membranes of the basal epidermal cell layer. Phenotype analysis of AQP3 null mice showed dry skin and delayed barrier recovery after removal of the stratum corneum [20][21][22]. These defects were attributed to the absence of AQP3-facilitated glycerol transport, resulting in reduced stratum corneum and epidermal cell glycerol content [20,21].…”
Section: Aqp3 Deletion In Mice Prevents Skin Tumor Formationmentioning
confidence: 99%
“…1E). Mice lacking AQP3, which is normally expressed in the basal layer of keratinocytes in epidermis, manifest reduced stratum corneum hydration and skin elasticity, and impaired stratum corneum biosynthesis and wound healing (Ma et al, 2002). The mechanism responsible for the skin phenotype in AQP3 deficiency involves reduced epidermal cell skin glycerol permeability, resulting in reduced glycerol content in the stratum corneum and epidermis (Hara and Verkman, 2003).…”
Section: Aqp Roles Related To Aqp-facilitated Glycerol Transportmentioning
confidence: 99%